Pengenalan Struktur Website, Tools, dan Karir Web Developer pada Siswa-Siswi SMK Swasta Jambi Medan - Ruziq, Fahmi; Wayahdi, M. Rhifky; Ginting, Subhan Hafiz Nanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Introduction to Website Structure, Tools, and Web Developer Careers is a community service activity carried out at the Jambi Medan Private Vocational School. This activity aims to provide basic knowledge about website development to SMK students, introduce tools and tools used by Web Developers, and discuss potential careers in this field. Activity methods include preparation of plans, introductions, presentations, demonstrations, making portfolios, discussions, and evaluations. This activity was held at a school location involving 20 students as participants. The results and discussion show that this activity had a positive impact on the participants. They gain a basic understanding of website structure and tools used in web development. The motivation to learn more in the field of web development has also increased, and this course provides an initial guide to building simple websites. Students feel better prepared to enter the technological world of work with potential careers as Web Developers or Web Designers. This activity helps them in preparing themselves for a future that is more connected with technology.